GIS In The Hydromorphology Analysis of Selected Meanders of The River Vardar - Kuzmanoski, Arse; Gorin, Svemir; Radevski, Iran; Markoski, Blagoja; Dimitrovska, Olgica; Manevska, Emilija (My University, 2025)
This paper aims to determine the hydromorphological changes of selected meander sectors of the largest river in the Republic of North Macedonia, the Vardar River using GIS. The meandering process is a significant dynamic in the hydrological studies of river systems. Covering a period of 59 years (1964-2023), in the study of the meandering process of selected three meander sectors in river Vardar, topographic maps with a scale of 1:50000, geological maps with a scale of 1:100000 and satellite images from the Landsat mission (1983-2013) and the Sentinel-2 mission (2018-2023) were used, which resulted in their processing and analysis. The planimetric characteristics that were analyzed for meandering are the width of the river channel, sinusoidality, radius of curvature, width of the meander section, slope and migration of the riverbed. In the period between 1964 and 2023, all three meander sectors have experienced significant changes in all parameters, with large changes in the width and length of the meander sectors, accompanied with significant lateral erosion on both coastal sides consistently. The hydromorphological changes that have occurred also differ in the different time periods of action, where each period is characterized by certain spatial changes. Understanding the hydromorphological changes in the meandering process has a significant role in predicting future changes in the flow of the riverbed in order to reduce and possibly prevent future potential impacts on the space.
Keywords: GIS; Satellite Images; meandering; Vardar River